EVALUASI DAN DESAIN SISTEM INFORMASI AKUNTANSI PEMUNGUTAN DAN PENYETORAN PPN DALAM UPAYA MENINGKATKAN EFISIENSI KINERJA SUBDINAS PERPAJAKAN PADA PT. PELABUHAN INDONESIA III (PERSERO) CABANG TANJUNG PERAK - Anindya Retno Wardhani; A.A Gde Satia Utama (Universitas Airlangga, 2016)
Branch of PT Pelabuhan Indonesia III (Persero) in Tanjung Perak is one of the institution body that appointed by the Government to carry out the collection and remittance of WAPU VAT according to PMK No. 85 / PMK.03 / 2012 (amended by PMK No. 136 / PMK.03 / 2012). WAPU VAT collection and deposit system are inefficient because it requires a lot of time and effort when it comes to input the data entry of tax invoice, printing Tax Deposit and sent it to Bank Perception. Three steps activities need to be done more than once. Therefore, Branch of PT Pelabuhan Indonesia III (Persero) in Tanjung Perak need the collection and remittance of the WAPU VAT system that sufficient to improve the efficiency of tax suboffices performance.This research aims to design the accounting information system for collecting and depositing process WAPU VAT. WAPU VAT Deposit using e-tax payment application are expected to overcome the problems that will arise in the WAPU VAT system deposit.Exploratory qualitative approach with case study method chosen in order to dig up the real problem occurs and find a solution. This research are expected to contribute significantly towards Branch of PT Pelabuhan Indonesia III (Persero) in Tanjung Perak as a research subject. In addition, the implementation of draft e-tax application payment system are expected to improve efficiency process of collection and remittance of WAPU VAT. Keyword : System Design, Wapu VAT, Efficiency, e-tax payment